CIL:40996, Rattus rattus, fibroblast. In Cell Image Library ... - Palade, George E. (UC San Diego Library Digital Collections, 2021)
Transmission electron micrograph of a thin section of a fibroblast from the ventricular myocardium of a rat showing a transverse view of rough endoplasmic reticulum (RER, sometimes termed granular endoplasmic reticulum). The 'rough' or 'granular' term refers to the membrane-attached polyribosomes (also known as polysomes). RER-associated polyribosomes are the sites of synthesis of proteins secreted into the RER cisternae and destined for export from the cell. ... : Original 3.25 in. x 4 in. lantern slides were scanned at 600dpi. ...